Who are the Promise Keepers?: understanding the Christian men's movement - Abraham, Ken (Doubleday, 1997)
Ken Abraham helped Jim Bakker pen his comeback book I Was Wrong, and now he has set to examining the phenomenal Christian men's movement. Although the Promise Keepers have succeeded in grounding and re-grounding tens of thousands of American men in old-fashioned Christian values, they have also raised the hackles of some who fear their anti-abortion, anti-gay, Republican leanings. Abraham takes these issues up one by one, answering each through profiles of the group's leaders, interviews with attendees, and commentary on the group's influence and direction. Essential reading for a future Promise Keeper.